2018
DOI: 10.1080/14789949.2018.1508486
|View full text |Cite
|
Sign up to set email alerts
|

Building from the ground up: exploring forensic mental health staff’s relationships with patients

Abstract: Recovery-orientated care is becoming generally accepted as the best practice, and continued development in the ways it is practiced is necessary to ensure improvement of ongoing care. Forensic patients often experience double stigmatization (the dual stigma of mental illness and offending behaviour) and during admission to hospital may lose touch with their community supports. While working through their personal recovery, patients develop therapeutic relationships with their multidisciplinary team members. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 33 publications
(50 reference statements)
1
38
0
Order By: Relevance
“…Furthermore, as identified in the documentation reviewed in our study, there is a tendency for nurses to take a paternalistic role with forensic patients which is expressed as “control, rule enforcement, and parenting behaviours” (Marshall & Adams, 2018). The NCRMD finding suggests that as a society, we have taken an individual's responsibility for their actions and committed to supporting their return to full citizenship.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, as identified in the documentation reviewed in our study, there is a tendency for nurses to take a paternalistic role with forensic patients which is expressed as “control, rule enforcement, and parenting behaviours” (Marshall & Adams, 2018). The NCRMD finding suggests that as a society, we have taken an individual's responsibility for their actions and committed to supporting their return to full citizenship.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is the 'social skin' that can be powerful in transforming identities (Winship, 2000, p.176). For example, positive interpersonal interactions contribute towards social connectedness (Baumeister and Leary, 1995) and positive therapeutic relationships can promote wellbeing (McKeown et al, 2016a;Marshall and Adams, 2018). Positive and supportive social environments are particularly important when diminished social networks are found to negatively influence wellbeing (Kawachi and Berkman, 2001;Hare-Duke et al, 2018).…”
Section: Forensic Mental Health: Secure Carementioning
confidence: 99%
“…In the shorter term, participants reported that staff could play an important role in providing reassurance to users. The suggestion that staff could lead by example by trialing the devices themselves reflects the role of staff as positive role models in inpatient services [38] and is a practical approach to alleviating user concerns.…”
Section: Discussionmentioning
confidence: 99%